Association between resiliency and posttraumatic growth in firefighters: the role of stress appraisal. Issue 1 (2nd January 2016) - Ogińska-Bulik, Nina; Kobylarczyk, Magdalena
Abstract : The purpose of this study was to establish the relation between resiliency and the level of positive changes, comprising posttraumatic growth in a group of firefighters experiencing job-related traumatic events and the mediating role of stress appraisal in this relation. The study was performed on a group of 100 firefighters from firefighting and rescue brigades, out of which 75 admitted to experiencing a traumatic event. Firefighters covered by the study were on average 31.51 years old ( SD  = 6.34). A Polish version of Posttraumatic Growth Inventory, the Resiliency Assessment Scale and Stress Appraisal Questionnaire were used in the study. The results have shown that 22.7% of firefighters displayed low, 58.6% average and 18.7% high intensity of positive changes resulting from a traumatic event. Resiliency poorly correlates with posttraumatic growth expressed in changes in self-perception, and strongly correlates with stress appraisal, negatively correlates with threat and harm/loss and positively correlates with challenge. Appraisal of stress as a threat and challenge appeared to be mediators of the relationship between resiliency and posttraumatic growth.